AStudy on Customer Acceptability of Online Payment Systems in Indonesia - Yunia Dwie Nurcahyanie; Eva Rosita; Patria Winahyu Binantoro; Suharyanto Suharyanto (Tibuana, 2022)
The finance industry is increasingly promoting innovation as a means of growth. It is thought to have created advancements that make transactions easier for users through the mobile banking function. The customer's adoption is also aided by several internal elements at the customer's disposal. This is a quantitative study in Indonesia to determine the link between perceived helpful factors, perceived ease of use, attitude toward usage, and behavioural intention. The data analysis approach used in this study is SEM-PLS. For example, consumer attitude and behaviour, the attitude variable in mobile banking may streamline the transaction process, feels enjoyable, and is easy to use, whereas the online payment application feels simple and ensures its anonymity. Users will find it simple to use the program for online payments, transactions will be secure, and payments for online shops will be considerably more manageable.